Indian Shoppers' Attitude Towards Grocery Shopping Apps: A Survey Conducted on Smartphone Users. Issue 2 (December 2019) - Chakraborty, Debarun
The smartphone users in India have been growing up for the past few years, and the research companies have predicted that it would still grow. Due to the advancement of technologies, affordable prices and various applications in the web stores, a large number of people are attracted towards smartphones. The goal of this study is to find out the approach of Indian shoppers towards grocery shopping apps. The Indian shoppers' attitude towards grocery shopping has still not been analysed by many, and this domain is still largely untapped. The theory of planned behaviour (TPB) and the technology acceptance model (TAM) models have been provided proper factors to analyse the shoppers' intention. The researcher has collected responses from various respondents with the help of a properly structured questionnaire, and a simple random sampling tool has also been used to select the respondents. Exploratory factor analysis and multiple regression analysis have been used to find out the outcomes. The outcomes of the study inform that attitude, perceived behavioural control, perceived usefulness and perceived ease of use have a positive and significant impact on intention. Subjective norms, however, do not have a significant effect on intention.